The Relationship Of The History Of Exclusive Breastfeeding and Complementery Feeding (MP-ASI) With The Incident Of Stunting In Toddler Children 24-59 Months - Putri Nelly Syofiah; Furwasyih, Dian; Femi, Nur; Gina Muthia; Ises Reni; Afrizal (International Health Sciences Journal, 2024)
The World Health Organization 2021 estimates the prevalence of stunting worldwide at 22% or as many as 149.2 million. In Indonesia, the prevalence of stunting is 21.6%. Padang City in 2022 has a stunting incidence rate of 19.5%, Ikur Koto Health Center has the highest percentage of stunting toddlers at 16%. Exclusive breastfeeding and appropriate complementary foods (MP-ASI) can contribute to supporting the health of children under five who can help in stunting prevention. The purpose of this study was to determine the relationship between the history of exclusive breastfeeding and complementary foods (MP-ASI) with the incidence of stunting in children under 24-59 months old in Koto Pulai Village, Ikur Koto Padang Health Center Working Area. This type of research is analytical with a cross sectional design. The population in this study was all mothers who had children under five 24-59 months in Koto Pulai Village, Ikur Koto Padang Health Center Working Area, totaling 40 children under five. The study sample amounted to 40 children under five 24-59 months with cluster ramdom sampling technique. The research instrument used was a questionnaire with a Chi-square test used for data analysis. The results of this study showed that 65.0% of children under 24-59 months old were stunted, 67.5% were not given exclusive breastfeeding and 62.5% were not given complementary milk. The results of statistical tests showed that there was no relationship between the history of exclusive breastfeeding p-value (0.480) and complementary foods (MP-ASI) p-value (0.864) with the incidence of stunting in children under five 24-59 months. The conclusion of this study, there are many factors that cause stunting in children under five, such as nutritional intake of toddlers, infectious diseases, food availability, socioeconomic factors, knowledge of maternal nutrition and others. It is expected for mothers to further increase full exclusive breastfeeding and provide complementary feeding appropriately.